Population Data Management Information System Of Population And Civil Registration Department - Nurul Latifah; Arizona Firdonsyah (Universitas Muhammadiyah Sidoarjo, 2021)
Population data is the main supporting component needed in data processing in the population office, population data must be recorded and managed so that it becomes a complete, structured and clearly organized database. The data that has been successfully obtained is used for monitoring the population in the environment. The Sleman Regency Population and Civil Registration Office has been using various systems based on each sector, but with this there are still some obstacles faced in the process of collecting population data in Sleman Regency. The purpose of this research is to describe the implementation of the Population Administration Information System in the Management of Identity Cards (KTP) at the Department of Population and Civil Registration in Sleman Regency. Data collection was carried out by the stages of field studies, literature studies, data collection by means of interviews to observation, data processing, then analysis and conclusions. The data were analyzed qualitatively and quantitatively. This research is also used as material for an overview of the flow of the existing system in the Office of Population and Civil Registration (DUKCAPIL) of Sleman Regency, regarding the feasibility and efficiency of database management from systems related to population data in Sleman Regency. The results of this study are in the form of a data entry flow design to an information system that can be used as a reference or guide and produce physical forms in the form of KIA, KK and KTP in the Department of Population and Civil Registration of Sleman Regency.